Principles of lesson planning: a guide for student teachers. - Piñeiro Ruíz, Milagro (2012)
This article attempts to guide students of Teaching English as a Foreign Language at the Universidad de Costa Rica, Sede de Occidente, in the process of planning. The paper presents the basic principles and components of lesson planning by organizing them into three different stages: before planning, while planning, and after planning. Also, the article pretends to motivate student teachers in the field of action research as a way to grow professionally.